PENGARUH KOMPETENSI, LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DI UP PTSP (Studi Kasus Kota Administrasi Jakarta Barat) - Aksan, Ahmad; Djati, S. Pantja (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
This study aims to examine and analyze the influence of competency, work environment  toward  job satisfaction, competency, work  environment toward job perpormance and job satisfaction toward job perpormance the employees of UP PTSP West Jakarta Design research using quantitative research methods explanatory, with a population all PNS UP PTSP West Jakarta. The sampling technique using simple random sampling The sample are used 190 respondents. Mechanical analysis using Structural Equation Modelling (SEM) with software Linear Structural Relationship (LISREL), Based on results of data processing and analysis showed that the variable of competency and work environment have a significant positive effect on job satisfaction.Competency has a significant positive effect on job performance, while work environment has positive but not significant effect on job performance. Job satisfaction has significant positive effect on job performance. So in this study that variables most influence on job performance is higher variables competency and job satisfaction